Heavy metal induced regulation of plant biology: Recent insights. Issue 3 (16th May 2022) - Sharma, Anket; Kapoor, Dhriti; Gautam, Shristy; Landi, Marco; Kandhol, Nidhi; Araniti, Fabrizio; Ramakrishnan, Muthusamy; Satish, Lakkakula; Singh, Vijay Pratap; Sharma, Priyanka; Bhardwaj, Renu; Tripathi, Durgesh Kumar; et al.
Abstract: The presence of different forms of heavy metals in the earth crust is very primitive and probably associated with the origin of plant life. However, since the beginning of human civilisation, heavy metal use and its contamination to all living systems on earth have significantly increased due to human anthropogenic activities. Heavy metals are nonbiodegradable, which directly or indirectly impact photosynthesis, antioxidant system, mineral nutrition status, phytohormones and amino acid‐derived molecules. Due to the toxic behaviour of some heavy metals, the endogenous status of chemical messengers like phytohormones may get significantly influenced, leading to harmful impacts on plant growth, development and overall yield of the plants. It has been noticed that exogenous application of phytohormones, that is, abscisic acid, salicylic acid, auxins, brassinosteroids, cytokinins, ethylene and gibberellins can positively regulate the heavy metal toxicity in plants through the regulation of the ascorbate–glutathione cycle, nitrogen metabolism, proline metabolisms, transpiration rate, and cell division. Furthermore, it may also restrict the entry of heavy metals into the plant cells, which aids in the recovery of plant growth and productivity. Besides these, some defence molecules also assist the plant in dealing with heavy metal toxicity. Therefore, the present review aims to bridge the knowledge gap in this context and present outstanding discoveries related to plant life supportive processes during stressful conditions including phytohormones and heavy metal crosstalk along with suggestions for future research in this field.